Possibilities for a Positive Change in the Body Image of Students in Dance-Motor Training - Gutko, A; Kuzminykh, L; Suvorova, O (KnE Life Sciences, 2018)
This article presents a study on the effectiveness evaluation of the author’s program of dance-motor training aimed at developing a positive image of the physical self in adolescence. The authors used a comprehensive approach to assess the effectiveness of training: the types of psychological problems, the characteristics of the image of the physical self, and the functional state of the participants in the training were monitored. The study involved 96 students from Nizhny Novgorod universities aging from 18 to 25. The researchers used the methods of the drawing test ‘Human figure’ (K. Mahover, F. Gudinaf); the test of twenty statements ‘Who Am I’ (M. Kun, T. McPartland); and the method of computer campimetry for assessing the functional state of the body by the function of color-diffusion (SA Polevaya). The self-body image of the subjects in the experiment was characterized by weak integration and awareness; negative and disharmonious deep self-esteem; low values of awareness of one’s own uniqueness; and the maximum limit of the green color was detected in more than half of the subjects (61.45%). Dance-motor training was based on the methodological principles of the integrative-holistic and syndrome-factor approach to mental disorders, developed by A.R. Luria. The development of the psychomotor sphere of a personality was considered as a trigger mechanism for restoring the interaction between the psychological and physiological sub-systems of mental activity. The dependence of the content and structure of mental processes on sociocultural experience (i.e., world artistic culture) was actualized. The mechanism of the regulating role of an image and speech in building the movement has become more active. Dance-motor trainings with students were conducted over the course of a year. We used methods of body-oriented psychotherapy, vegetotherapy, and dance-motor therapy, including contact improvisation. The dance-motor training included warm-ups (aerobic and anaerobic exercises, muscle-stretching exercises); the thematic study of muscle clamps; and choreographic performances (learning movement stereotypes, free and contact improvisation). In the control experiment, a statistically significant conjugate dynamics was observed for the majority of the studied parameters (0.001). Keywords: body image, dance-motor training, students